Vitamin A Derivative Etretinate Improves Bleomycin-induced Scleroderma - Takaharu Ikeda; Toshio Ohtani; Fukumi Furukawa (Allergology International, 2005)
Background: We recently demonstrated that the vitamin A derivative etretinate was clinically effective in the treatment of skin disorders in patients with systemic sclerosis (SSc). The aim of the present study is to investigate whether the oral treatment with etretinate improves sclerosis in bleomycin (BLM)-induced sclerotic skin mice. Methods: BLM-induced sclerotic skin mice were treated orally with 10 mg/kg etretinate for 1 to 28 days. One control group received only the vehicle, 50 μl peanut oil, while another group received no agents. BLM-treated skin was removed and dermal thickness was measured histologically. Histopathological observation and TUNEL assay were also studied. Messenger RNA (mRNA) ratios for procollagen α 1 (I) chain to β actin from etretinate-treated and control mice were quantified at 1, 6, 14, and 28 days post-treatment, using quantitative RT-PCRs. Results: There was a significant decrease in mean dermal thickness (P < 0.05) and changes in collagen bundles in the etretinate-treated mice group for a 28-day period compared to control groups. TUNEL assay showed that the density of TUNEL-positive cells in the dermis of etretinate-treated mice for a 14-day period was significantly increased (P < 0.05). The ratio of procollagen α 1 (I) chain to β actin mRNA from etretinate-treated mice for a 1-day period decreased significantly compared to that of the control mice, but the ratio from etretinate-treated mice for a 14-day period increased significantly (P < 0.05). Conclusions: Etretinate improved BLM-induced scleroderma. These results suggest that etretinate can be applied to the treatment of SSc skin disorders.